APSH YI-04 EXPANSION OF IMMUNOSENESCENT T CELL FRACTION IN CHRONIC KIDNEY DISEASE PATIENTS: EXPLORING NEW PATHOGENIC MECHANISMS OF INCREASED ARTERIAL STIFFNESS. (September 2016) - Youn, Jong-Chan; Yu, Hee Tae; Kim, Hyeon Chang; Choi, Suk-Won; Han, Seong-Woo; Ryu, Kyu-Hyung; Shin, Eui-Cheol; Park, Sungha
Abstract : Objective: Chronic kidney disease (CKD) is associated with increased arterial stiffness, which is a well-known predictor of future cardiovascular events. However, the underlying mechanism of arterial stiffening in CKD is not well known. Accelerated immune aging, characterized by expansion of immunosenescent T cell fraction might be involved in the pathogenesis of arterial stiffening in CKD. We aimed to evaluate the relationship between arterial stiffness and immunosenescent T cell (CD8 + CD57 + or CD8 + CD28 - T cell) fraction in patients with CKD. Design and method: Four hundred and twenty-nine consecutive hypertensive patients with CKD (266 male, mean age 61 ± 10 years) who registered in Cardiovascular and Metabolic Disease Etiology Research Center - High Risk Cohort (CMERC-HI, NCT02003781) were enrolled. Arterial stiffness was evaluated by pulse wave velocity (PWV) and the frequency of CD57 + or CD28 - senescent T cells in peripheral blood lymphocytes were examined by multicolor flow cytometry. Results: Immunosenescent T cell fraction showed significantly increased tendency according to CKD stages (CD8 + CD57 + T cell fraction, p < 0.001: 40.8 ± 16.4% in stage 1, 47.5 ± 17.0% in stage 2, 48.3 ± 16.0% in stage 3, 51.9 ± 19.3% in stage 4, 52.0 ± 18.0% in stage 5, CD8 + CD28 - T cell fraction, p < 0.001: 46.8 ± 17.9% in stage 1, 50.4 ± 19.7% in stage 2, 50.7 ± 17.7% in stage 3, 60.2 ± 19.3% in stage 4, 60.0 ± 16.5% in stage 5). Multivariate analysis revealed that CD8 + CD57 + T cell fraction is independently associated with PWV even after adjustment with age, gender, body mass index, renal function and systolic blood pressure (β = 0.102, p = 0.038). Conclusions: In CKD patients, CD8 + CD57 + T cell fraction are expanded and independently associated with increased arterial stiffness. These findings may explain the role of immunosenescence in the pathogenesis of accelerated arterial stiffening in patients with CKD.